2016
DOI: 10.1111/eci.12626
|View full text |Cite
|
Sign up to set email alerts
|

The controversy over the use of cholesteryl ester transfer protein inhibitors: is there some light at the end of the tunnel?

Abstract: Background According to epidemiological studies, there is no clear relationship between the plasma cholesteryl ester transfer protein (CETP) concentration and the development of atherosclerosis in human populations. Although some studies suggest that increased CETP activity relates to undesirable profiles of plasma lipoproteins, promoting an anti-atherogenic plasma lipoprotein profile by drugs that inhibit CETP has not succeeded in preventing atherosclerosis in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 85 publications
(152 reference statements)
0
6
0
4
Order By: Relevance
“…CETP is synthesized in the liver and secreted into the plasma, and its activity influences the atherogenicity of the lipoprotein profile and cholesterol efflux in macrophages (Tall et al, 2008). In humans, CETP deficiency characteristically exhibits high HDL and low LDL levels (Brown et al, 1989;Inazu et al, 1994), but the correlation of plasma CETP level with atherosclerosis remains controversial and has not yet been clearly demonstrated in studies involving human populations (Dullaart et al, 2007;Quintao, 2016). Some species, such as rats and mice, do not express CETP, and transfer of cholesterol and CE to the liver mainly via HDL (Kingwell et al, 2014).…”
Section: Cholesteryl Ester Transfer Protein (Cetp)mentioning
confidence: 99%
See 1 more Smart Citation
“…CETP is synthesized in the liver and secreted into the plasma, and its activity influences the atherogenicity of the lipoprotein profile and cholesterol efflux in macrophages (Tall et al, 2008). In humans, CETP deficiency characteristically exhibits high HDL and low LDL levels (Brown et al, 1989;Inazu et al, 1994), but the correlation of plasma CETP level with atherosclerosis remains controversial and has not yet been clearly demonstrated in studies involving human populations (Dullaart et al, 2007;Quintao, 2016). Some species, such as rats and mice, do not express CETP, and transfer of cholesterol and CE to the liver mainly via HDL (Kingwell et al, 2014).…”
Section: Cholesteryl Ester Transfer Protein (Cetp)mentioning
confidence: 99%
“…Therefore, CETP-containing species, such as hamsters, monkeys, and ApoB/CETP double-transgenic mice, have been used to evaluate the effects of CETP expression on lipid metabolism and atherosclerosis development (Honzumi et al, 2010;Kingwell et al, 2014). Numerous studies suggest that CETP may have pro-or antiatherogenic properties depending upon the pathophysiological settings, and whether the CETP inhibition-induced lipoprotein changes exert anti-atherogenic activities remains a matter of debate (Dullaart et al, 2007;Ghosh and Ghosh, 2012;Quintao, 2016). LXRα has an essential role in the induction of CETP, whereas LXRβ activation has only a minor effect (Honzumi et al, 2010).…”
Section: Cholesteryl Ester Transfer Protein (Cetp)mentioning
confidence: 99%
“…In animal models, CETP inhibition protected transgenic mice expressing human CETP ( 1 ) as well as rabbits naturally expressing CETP against atherosclerosis ( 3 , 4 ). The CETP link with atherosclerosis and infection has been reviewed in humans ( 5 ), and lower plasma CETP concentrations occurred in patients who did not survive sepsis compared to survivors. Additionally, a positive correlation between plasma CETP concentration and sepsis survival rate was reported ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a positive correlation between plasma CETP concentration and sepsis survival rate was reported ( 6 ). CETP is involved in the inflammatory response in mice expressing the human CETP gene (huCETP), which is more resistant to endotoxemia and experimental sepsis than in wild type mice ( 5 , 7 , 8 ). However, these results diverge from more recent results concluding that human CETP worsens inflammation and sepsis in mice ( 9 ), with CETP inhibition improving the survival rate in human sepsis ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…High plasma concentrations of CETP are associated with low HDL-C which led to the development of CETP inhibitors that raise HDL-C levels and reduce atherosclerosis in experimental animals [ 17 20 ]. However, trials in humans using CETP inhibitors failed to protect against cardiovascular diseases [ 17 , 20 22 ] and one of them (torcetrapib) increased the incidence of cancer and infection [ 20 , 22 ]. In addition, recent in vivo experiments and human studies have suggested that CETP may have beneficial actions during acute inflammatory states [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%